Journal Management Services at Padjadjaran University Knowledge Management Center - Osama Muhammad Fikri; Evi Nursanti Rukmana; Sukaesih; Samson CMS (Universitas Airlangga, 2022)
The Open Journal System (OJS) in universities is used to increase university publications by providing open access to journals to keep knowledge alive. This study aims to determine the Open Journal System (OJS) service at the Knowledge Management Center of Padjadjaran University through collection analysis, retrieval system, and service model. This study uses descriptive qualitative research methods. The results showed that the Open Journal System collection of the Knowledge Management Center Universitas Padjadjaran amounted to 105 journals from 14 faculties. Each journal represents the scientific study program in each faculty. Users in the retrieval system can determine information from the articles they are looking for, use features, and determine the right query, information search results, and additional records of information search results. The Knowledge Management Center of Padjadjaran University provides information and consultation on journal indexation, and records journals, and provides guidance for journals that will apply for accreditation/reaccreditation. The OJS service model at the Unpad Knowledge Management Center has been carried out well using regular communication and sharing information with journal managers regarding journal management. The Unpad Knowledge Management Center has provided a good service model in the form of guidance, direction, or consultation regarding journal management to university journals.